‘A bridge over troubled water’: a case report - D’Amario, Domenico (Eur Heart J Case Rep, 2021)
BACKGROUND: Myocardial bridge (MB) is the most common inborn coronary artery variant, in which a portion of myocardium overlies a major epicardial coronary artery segment. Myocardial bridge has been for long considered a benign condition, although it has been shown to cause effort-related ischaemia. CASE SUMMARY : We present the case of a 17-year-old female patient experiencing chest pain during physical activity. Since her symptoms became unbearable, electrocardiogram and echocardiography were performed together with a coronary computed tomography scan, revealing an MB on proximal-mid left anterior descending artery. In order to unequivocally unmask the ischaemic burden lent by MB, the patient underwent coronary angiography and physiological invasive test: instantaneous wave-free ratio (iFR) and fractional flow reserve (FFR) were calculated, both at baseline and after dobutamine infusion (5 µg/kg/min). At baseline, iFR value was borderline (= 0.89), whereas after dobutamine infusion and increase in the heart rate, the patient suffered chest pain. This symptom was associated with a decrease in the iFR value up to 0.77. Consistently, when FFR was performed, a value of 0.92 was observed at baseline, while after inotrope infusion the FFR reached the haemodynamic significance (= 0.79). Therefore, a medical treatment with bisoprolol was started. DISCUSSION : Our clinical case shows the importance of a comprehensive non-invasive and invasive assessment of MB in young patients experiencing chest pain, with significant limitation in the daily life. The coronary functional indexes allow to detect the presence of MB-derived ischaemia, thus guiding the decision to undertake a medical/surgical therapy.